Energy band modification for UV photoresponse improvement in a ZnO microrod-quantum dot structure. Issue 1 (22nd December 2015) - Wu, Chunxia; He, Zijuan; Lu, Junfeng; Dai, Jun; Xu, Chunxiang
Abstract : The ZnO microrod/QDs hybrid structure creates an efficient charge transfer for superior photoresponse through energy band modification. Abstract : In this paper, ZnO quantum dots (QDs) were decorated on an individual ZnO microrod surface to construct a UV photodetector with good performance. The perfect hexagonal ZnO microrod creates a totally internal reflective configuration for enhanced light–matter interaction while the quantum confinement of the QDs extends the energy bandgap for broader spectral response. More importantly, the QD modified microrod constructs a favorable charge transfer system for effective UV photoresponse. As the ZnO QDs were decorated on the microrod, the photocurrent and light-to-dark current ratio were increased by about 2 magnitude orders while the response and recovery speed were accelerated by more than 1 order of magnitude. The material preparation, device fabrication, optoelectronic behavior and mechanism are investigated in detail. This research presents a facile and viable approach to design optoelectronic devices by integrating quantum dots into the same bulk semiconductor.